Gaps in reporting greenhouse gas emissions by German hospitals: a systematic grey literature review - Quitmann, Claudia; Sauerborn, Rainer; Herrmann, Alina (Sustainability, 2021)
To mitigate the negative (health) consequences of climate change, the Paris Agreement demands a radical reduction of greenhouse gas (GHG) emissions. The health sector contributes considerably to climate change worldwide. In Germany it is responsible for 6.7% of national GHG emissions. The transition to low-carbon hospitals requires detailed knowledge of the amount and sources of GHG emissions. This study aimed at capturing the status quo of GHG emission reporting by German hospitals and at examining characteristics of the reports. Therefore, we performed a grey literature review with pre-defined inclusion and exclusion criteria. The search strategy comprised hand-searching specific databases, targeted websites and web search engines via a standardized set of search terms. We found 232 German hospitals reporting their GHG emissions, representing 12% of all hospitals. Yet, only 62 hospitals (3%) met the inclusion criteria for further analysis. These reports do not comprise all energy-related GHG emissions, omit GHG emissions occurring up- and downstream of hospitals and mainly include CO2, but leave out other GHG. Consequently, there are severe gaps regarding GHG emissions reports of German hospitals. If Germany wants to comply with the Paris Agreement, hospitals need to be obliged to follow a standardized methodology to report and reduce GHG emissions.
Gesehen am 04.05.2021